Nasal Nitric Oxide Measurement and a Modified PICADAR Score for the Screening of Primary Ciliary Dyskinesia in Adults with Bronchiectasis - Rademacher, J.; Buck, A.; Schwerk, N.; Price, M.; Fuge, J.; Welte, T.; Ringshausen, F. C. (Pneumologie, 2017)
Background Determining the underlying diagnosis is essential for the targeted and specific treatment of bronchiectasis. Primary ciliary dyskinesia (PCD) is a rare genetic disease, which is characterized by abnormalities in ciliary structure and/or function and which may result in bronchiectasis. The disease is probably underestimated among adults with bronchiectasis due to the fact that extensive diagnostic testing is required and that the recognition of PCD is low. Objective To evaluate a feasible screening algorithm for PCD among adults with bronchiectasis.Methods Data from all patients who presented to our bronchiectasis outpatient clinic from June 2010 until July 2016 were retrospectively analysed from our database. Nasal NO (nNO) and a modified PICADAR score (PrImary CiliAry DyskinesiA Rule) were measured and compared in the two groups of PCD-bronchiectasis and non-PCD-bronchiectasis.Results 185 of 365 patients (75 males, 110 females) had a sufficient measurement of nNO concentration and complete clinical data and were eligible for analysis. The mean (SD) nNO concentration in nL/ml was significant lower in the PCD group compared to the non-PCD group (25 [31] and 227 [112] nL/min, respectively; p < 0.001). A nNO level of 77 nL/min had the best discriminative value to differentiate between the two groups. Patients with PCD had a significant higher modified PIDACAR score than patients without PCD (5 2 and 1 1, respectively [p < 0.001]). Using ROC curve analysis, the modified PICADAR score of 2 had the best discriminative value with a sensitivity of 1.00 and a specificity of 0.89. Conclusions Low nNO concentration and the modified PICADAR score are suitable and cheap screening tests for PCD in adults with bronchiectasis.Hintergrund Um Patienten mit Bronchiektasen gezielt und effektiv therapieren zu können, ist es notwendig die zugrunde liegende Ätiologie zu kennen. Die primär ciliäre Dyskinesie (PCD) ist eine seltene genetische Erkrankung mit Veränderungen in der Zilienstruktur und/oder -funktion, welche zu Bronchiektasen führen kann. Da die Diagnostik aufwendig, nur selten verfügbar und teuer ist, wird die PCD als Ätiologie für Bronchiektasen zum Teil erst spät erkannt und ist wahrscheinlich unterdiagnostiziert.Zielsetzung Evaluierung eines einfachen Screeningverfahrens für PCD in Patienten mit Bronchiektasen. Methoden Es wurden retrospektiv die Daten aller Patienten mit Bronchiektasen in der Spezialambulanz der Medizinischen Hochschule Hannover von Juni 2010 bis Juli 2016 analysiert. Das nasale NO (nNO) und der modifizierte PICADAR-Score (PrImary CiliAry DyskinesiA Rule) wurden gemessen und in den zwei Gruppen PCD-Bronchiektasen und Nicht-PCD-Bronchiektasen verglichen.Ergebnisse 185 von 365 Patienten (75 Männer, 110 Frauen) hatten eine suffiziente nNO-Messung sowie vollständige klinische Daten und konnten in die Analyse eingeschlossen werden. Der Mittelwert (SD) der nNO-Konzentration in nL/ml war signifikant niedriger in der PCD-Gruppe im Vergleich zu Nicht-PCD-Patienten (25 [31] und 227 [112] nL/min; p < 0,001). Ein nNO von 77nL/min ist der beste diskrimitative Wert um zwischen diesen beiden Gruppen zu unterscheiden. Patienten mit PCD zeigten einen signifikant höheren PICADAR score als Patienten ohne PCD (5 [2] und 1 [1], (p < 0,001)). Der beste diskrimitative Wert des modifizierten PICADAR-Scores lag bei 2 mit einer Sensitivät von 1,00 und einer Spezifität von 0,89. Schlussfolgerung Die Kombination aus niedrigem nNO und ein hoher modifizierter PICADAR-Score ist ein einfacher und kostengünstiger Screeningtest auf PCD bei Patienten mit Bronchiektasen.